2020
DOI: 10.2337/dc19-1803
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Associations of Chronic Kidney Disease in Community Participants With Diabetes: A 5-Year Prospective Analysis of the EXTEND45 Study

Abstract: To determine the incidence of and factors associated with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 in people with diabetes. RESEARCH DESIGN AND METHODSWe identified people with diabetes in the EXamining ouTcomEs in chroNic Disease in the 45 and Up Study (EXTEND45), a population-based cohort study (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) that linked the Sax Institute's 45 and Up Study cohort to community laboratory and administrative data in New South Wales, Australia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…The median occurrence time of CKD among type-II DM patients was 5 years, which is congruent with a study done in North America (4.4 to 4.7years) [ 9 ]. However, it’s deemed to be shorter than the findings of the studies done in the capital of Ethiopia (Addis Ababa) (5.9 years) [ 27 ], the UK (12years) [ 10 ], and Australia (5.7years) [ 16 ]. This could be ascribed to the quality of the service, the patients’ awareness about complications of DM, health-seeking behavior of patients’, their residency (all urban), and self-care practice were better among participants involved in the current study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median occurrence time of CKD among type-II DM patients was 5 years, which is congruent with a study done in North America (4.4 to 4.7years) [ 9 ]. However, it’s deemed to be shorter than the findings of the studies done in the capital of Ethiopia (Addis Ababa) (5.9 years) [ 27 ], the UK (12years) [ 10 ], and Australia (5.7years) [ 16 ]. This could be ascribed to the quality of the service, the patients’ awareness about complications of DM, health-seeking behavior of patients’, their residency (all urban), and self-care practice were better among participants involved in the current study [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the time-to-occurrence of CKD (the time at which patients developed CKD since they diagnosed with type II DM) varies across different studies. The median occurrence time of CKD was around 3.8-12 years worldwide [9,10,16,17]. In Africa, the incidence of CKD is estimated to be between 13.3-25% [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Winell [18], in a 1996-2012 study in Finland, found that diabetic patients have a higher incidence rate of HF, with a worse prognosis, than non-diabetic patients. Sukkar [19] studied 9,313 diabetic patients and found that 22.6% developed CKD during a mean follow up of 5.7 years. Advanced age and cardiovascular comorbidity, among other factors, were associated with an increased incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The global diabetes prevalence in 2019 was estimated to be 9.3% (463 million people), rising to 10.2% (578 million) by 2030 and 10.9% (700 million) by 2045 [1]. Poorly controlled diabetes can mediate multiple organ damage, leading to microvascular and macrovascular complications, including kidney failure, blindness, amputation, and cardiovascular disease (CVDs) [2] [3]. Despite the medical research of diabetes was already mature and the treatment was comprehensive, T2DM remained considered as an incurable disease, and patients with T2DM still suffered high rates of complications.…”
Section: Introductionmentioning
confidence: 99%